Assessment of Injury Risk in Professional Soccer Players: A Long-Term Study - Andreas Fousekis; Konstantinos Fousekis; Georgios Fousekis; Panagiotis Gkrilias; Yiannis Michailidis; Athanasios Mandroukas; Thomas Metaxas (Applied Sciences)
The aim of this study was to record and interpret external load parameters in professional soccer players in competitive microcycles with one or two matches per week, while investigating the interaction between training load and non-contact musculoskeletal injuries during training and matches. Musculoskeletal injuries in athletes are closely associated with workload fluctuations, particularly the acute:chronic workload ratio (ACWR) over preceding weeks. This study analyzed the physical workload of 40 high-level soccer players competing in the Greek championship across two seasons, encompassing 50 competitive microcycles, 60 official matches, and 300 training sessions. GPS-based assessments recorded total distance (TD), running speeds (15–20 km/h, 20–25 km/h, 25–30 km/h), accelerations (>2.5 m/s2), and decelerations (>2.5 m/s2). An independent sample t-test was conducted to compare injured and uninjured athletes, with statistical significance set at p < 0.05. Results showed that 20 injured athletes frequently exceeded the ACWR threshold (>1.3) compared to uninjured players. Analysis of the four weeks preceding the injury revealed that increased workload in high-intensity categories significantly contributed to non-contact injuries. Specifically, high running speeds of 15–20 km/h (p = 0.015), 20–25 km/h (p = 0.045) and >25 km/h (p = 0.008), as well as accelerations (p = 0.010), were linked to a higher risk of injury. The three-week ACWR model indicated statistically significant differences in the ACWR index for total distance (p = 0.033), runs at 15–20 km/h (p = 0.007), >25 km/h (p = 0.004), accelerations (p = 0.009), and decelerations (p = 0.013). In the two-week model, significant differences were found in runs at 15–20 km/h (p = 0.008) and >25 km/h (p = 0.012). In the final week, significant differences were observed in runs at 15–20 km/h (p = 0.015), >25 km/h (p = 0.016), and accelerations (p = 0.049). Additionally, running speeds of 25–30 km/h (p values between 0.004 and 0.016) played a key role in injury risk when limits were exceeded across all weekly blocks. These findings highlight the importance of monitoring ACWR to prevent injuries, particularly by managing high-intensity workload fluctuations in elite athletes.